3 kW narrow-linewidth all-fiber amplifier with near diffraction limited beam quality. (20th March 2019) - Chu, Qiuhui; Shi, Yi; Wen, Jing; Ouyang, Lie; Zhao, Lei; Wang, Jianjun; Lin, Honghuan; Jing, Feng; Tang, Chuanxiang
Abstract: A theoretical model is established to simulate the stimulated Brillouin scattering (SBS) effect in fiber amplifiers using white noise signal (WNS) phase-modulated seed. Based on the theoretical model, the influences of amplifier structure and cut-off frequency of WNS on SBS threshold are discussed in detail. Through theoretical analysis, optimized amplifier structure and phase modulation signal are achieved to suppress SBS, and a fiber laser based on a main oscillator power amplifier with counter-pumped scheme is established. The oscillator, with 3 dB spectral linewidth of 48 GHz, is produced by a WNS phase-modulated single-frequency seed. The amplifier uses a 915 nm diode laser pump and 25/400 Yb-doped optical fiber. The output power reaches 3.02 kW at 1064 nm, with 3 dB root-mean-square linewidth of 48 GHz. Amplified quality is obtained with M, M at maximum power.